Cost Effectiveness of Rivaroxaban versus Warfarin to Prevent Stroke in Iranian AF Patients - Gordan, Hesamaddin; Beyranvand , Mohammad Reza; Sheibani , Mehdi; Asadpur Piranfar , Mohamad; Pourhoseingholi, Mohamad Amin (Student Research in Translational Medicine, 2020)
Background and objectives: Atrial fibrillation (AF) is the most common sustained arrhythmia in adults which need anti-coagulant to prevent stroke. Due to high cost of Rivaroxaban compared to warfarin, it`s not prescribed as much as warfarin by physicians despite its superiority in intracranial hemorrhage. Therefore, this study aimed to evaluate the cost-effectiveness of rivaroxabane versus warfarin in preventing stroke in AF patients. Methods: This study is a cost-utility analysis with cost-effectiveness assessed by the incremental cost per quality-adjusted life-year (QALY). Two strategies were used to obtain the costs; the first was from available resources and the next was to collect data using a questionnaire. Utility values for obtaining ∆QALYs were sourced from published data. Finally the cost-effectiveness of Warfarin versus Rivaroxaban was assessed using an incremental cost-effectiveness ratio (ICER), which was calculated as the incremental cost per QALY (Quality-adjusted life year) gained. Results: A total number of 98 patients who met the inclusion criteria were answered the questionnaire. Mean annually physician visits were 4 times in rivaroxaban and 14 times in warfarin group. The patients in Warfarin Group checked their INR (international normalised ratio) 15 times a year, while the patients in Rivaroxaban group did not check at all. The wasting time for each physician visit and doing Lab test was approximately 3 hour. Total cost of Rivaroxaban in both private (16699000IRR) and public services (15755000IRR) were less than Warfarin in both private and public services (24233700 & 20345600 IRR). We analyzed the ΔQALYs of 7 different articles in which the mean ΔQALY was 0.21 (Variance: 0.0072). The Incremental cost per QALY per patient for warfarin in Private versus public services was 18514762 Rial /QALY, while the ICER between Rivaroxaban versus warfarin in both private and Public services was negative (-35879523.8 and -21860000 Rial/QALY). So the calculated threshold based on the per capita gross national product (GDP), which was 702576000 Rials (calculated at 42,000IRR/), showed that Rivaroxaban is more cost-effective than Warfarin. Conclusions The results of present study demonstrated that use of Rivaroxaban versus Warfarin in both public and private services is a cost-effective choice. So, due to its economic and potential benefits, it is recommended to prescribe Rivaroxaban rather than warfarin.